2013
DOI: 10.7314/apjcp.2013.14.9.5085
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature of Food and Beverage Intake Increases the Risk of Oesophageal Cancer in Xinjiang, China

Abstract: Background: The north-western region of China has a high incidence of oesophageal cancer. This study aimed to investigate whether the intake of food and beverage at high temperature is associated with the risk of oesophageal cancer among adults residing in this remote part of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…In the study by Cook-Mozzafari et al (1979) hot tea consumption was positively associated with the risk of squamous cell oesophageal cancer. Similar findigns were published from China (Tang et al, 2013). Castellsague et al (2000) replicated these findings in the pool analysis of oesophageal carcinoma in South America.…”
Section: Discussionsupporting
confidence: 67%
“…In the study by Cook-Mozzafari et al (1979) hot tea consumption was positively associated with the risk of squamous cell oesophageal cancer. Similar findigns were published from China (Tang et al, 2013). Castellsague et al (2000) replicated these findings in the pool analysis of oesophageal carcinoma in South America.…”
Section: Discussionsupporting
confidence: 67%
“…The number of EC cases diagnosed in the studies ranged from 47 to 1,310, with a total of 13,811 reported EC cases. Seventeen studies were conducted in China [ 13 , 19 , 20 , 25 - 38 ], six in Uruguay [ 11 , 16 , 39 - 42 ], three in Argentina [ 11 , 16 , 43 ], three in Brazil [ 11 , 16 , 44 ], three in Paraguay [ 11 , 16 , 45 ], three in India [ 46 - 48 ], three in Iran [ 15 , 49 , 50 ], two in British [ 8 , 51 ], one in Australia [ 12 ], one in Sweden [ 7 ], one in Greece [ 6 ], one in Kenya [ 52 ], and one in Japan [ 53 ]. Thirty studies reported results for men and women together, four reported the results for men and women separately, and three reported results for men only and two for women only.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 11 ] contained 4 kinds of drinks, and was, therefore, accounted as four independent reports. Another study [ 19 ] reporting tea, water and food was regarded as three reports. Two studies [ 13 , 20 ] conducted in two different areas of China were considered as two reports respectively, and another study [ 16 ] including two large multicenter case–control studies was treated as two reports.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous experimental and clinical studies have suggested that drinking beverages at high temperatures is a cause of esophageal cancer [ 39 , 40 ]. More tumors were observed and the size of esophageal papillomas was increased at temperatures of 70°C and above in a previous experimental study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%